Optimal investment decision making on the model of production enterprise with limited resources - Ivanenko, Tetiana; Hrushko, Viktor; Frantsuz, Anatolii; Грушко, Віктор Іванович; Француз, Анатолій Йосипович (LLC CPC Business Perspectives, 2018)
Investments are among the most important factors of national economic growth. Selection of optimal investment project is the first priority for any enterprise with limited financial resources. This study is dedicated to a choice among mutually exclusive projects, which are impossible to complete partially, so, one project must be chosen and all others must be rejected. An investor must find among all possible projects the one that allows to better achieve all investor's aims. A mathematical model of multi-purpose multi-criteria investor decision making is proposed for investment project selection problem. Efficiency and riskiness of studied projects are evaluated using such indicators as profit, rate of return, payback period, marginal cost of capital, also taking into account subjective characteristics, namely the investor's attitude towards financial risks, importance assessment of decision making criteria, etc. Decision making assessment methods for the situations of risk and uncertainty are applied to resolve the problem of optimal project selection, such as Wald's pessimistic criterion, maximax optimistic criterion, as well as Hurwicz's, Laplace's, Bayes-Laplace, Hodges-Lehmann criteria, and Savage's minimax risk criterion. Calculations carried out and results obtained indicate that the best investment project chosen that way will provide the highest absolute profit, despite certain disadvantages such as lower rate of return, longer payback period and higher risk than other projects. © Tetiana Ivanenko, Viktor Hrushko, Anatolii Frantsuz, 2018
Keywords: MCDM; investor strategies; decision matrix; project selection